Attitude towards rape victims and the perception of sex roles of male and female in Penang and Perlis - Teh, Yik Koon (Universiti Utara Malaysia, 1997)
The proclamation of the United Nation Decade for Women in 1975 has brought about an increase in acknowledgement of the role of women in development. Women are no longer viewed as just wives and mothers. They are now seen as contributors to the economic and social development of their countries. In Malaysia, the National Policy for Women has facilitated the assimilation of women into the mainstream of social and economic activities (Sixth Malaysia Plan 1991;413).In education, there is a reduction in sex differentials (Tey,1991;2). In 1980, the literacy rate among persons aged 20 to 29 years was 69% for females and 80% for males, while for those aged 40 and above, the rate was 23.1% and 61% respectively. At present, the rate is more equal. Primary school enrolment is universal. In secondary schools, the girls slightly outnumbered the boys and the tertiary level, female representation level was 44.3% in 1990 (Tey, 1991;2). However, in the area of employment, both in the public and private sector, their number is under-represented (see Phang, 1991; Puthucheary, 1991). Female workers represent only 32% of the labour force (Population and Housing Census of Malaysia,1991). An exploratory study by by Puthucheary in 1991 found that the traditional view of a woman's place is in the home" still dominates the thinking process of Malaysian men and women even though the importance of women's role in economic development has been acknowledged. Women's organizations in Malaysia like the Women Crisis Centre, the National Council of Women, the All Women's Action Group and the Women's Aids Organization believe that there is still discrimination against women's at work. At home, women are still seen as the inferior partner. These women's groups believe that one of the major factors for crimes against women like rape in Malaysia is due to the unequal status of women in society (Yen,1995). This believe is strongly supported by researchers carried out in the West, for example, studies on rape by Susan Brownmiller (1975), Smart and Smart (1978), Martin and Hummer (1993) and Burt (1991).The Consumer Association of Penang (1988) and the women's organizations in Malaysia also believe that the attitude of the Malaysian public towards the crime pf rape is also bias and misconceived. Some of the misconceptions of the problem of rape by the Malaysian society are: 1.The rape victim is usually a young, beautiful woman who dresses and behaves in a seductive manner. Thus, she deserves to be raped; 2. A woman usually get raped when they are out alone at night, especially at isolated places; 3.The typical rapist is a stranger; 4. He is usually mad or a dangerous psychopath, or he is under the influence of alcohol or drugs; 5. He is unable to control his sexual drives when he sees his victims. Thus, rape is also a spontaneous crime; 6. When a woman gets raped, it is her fault as she asked for it. The truths to the above misconceptions as shown by Teh (1997; 197-198) are: 1. Anybody can be a rape victim, including children and old people; 2. Rape can take place anywhere, including at home; 3. There is no definite characteristic to differentiate a rapist; 4. In many cases, the victims knew the rapists; 5. In many cases, the acts have been planned beforehand; 6. Researches have shown that the rapists come from a violent background; 7. Rape is an act of violence where the rapist felt the need to control someone who is perceived as inferior to him. This research has tried to find out the attitude towards rape victims and the perception of sex roles of male and female in north Malaysia; Penang and Perlis. This is to see if there is a relationship between their perception towards their sex roles and their attitude towards rape victims.